TEENAGER KNOWLEDGE OF SMAN 2 MAMUJU GIRLS ABOUT FACIAL BLEACHING CREAM - Nurfadhilah Reski; Wita Oileri Tikirik; Suryadi; I Kadek Dwi Swarjana (Media Inovasi Pendidikan dan Publikasi, 2023)
Whitening cream is a mixture of chemicals and/or other ingredients with the property of fading black spots on the skin. The total use of mercury through small-scale gold mining throughout Indonesia is estimated at 13.94 –192.53 tons/year. This is based on the estimated amount of mercury use in one location reaching 6.2 – 85.63 kg Hg/year. This research is descriptive research with a cross sectional approach design, namely research measuring variables only once at a certain time with a student population of SMAN 2 Mamuju and 193 willing respondents. The results of this research show that of the 193 respondents, 25 respondents had knowledge of 13.0%, 164 respondents did not know 85.0%, 4 respondents did not know 2.1%. It is recommended that this research provide education regarding safe cosmetics to the public, especially teenagers, to be more careful in choosing cosmetics that are safe and healthy to use, especially considering that there are many traders out there who cannot be held responsible for what they have done